2008
DOI: 10.1144/1354-079308-781
|View full text |Cite
|
Sign up to set email alerts
|

Geomechanics of polygonal fault systems: a review

Abstract: Layer-bound systems of polygonal faults are found in sequences of very fine-grained sediments that have typically undergone passive subsidence and burial. In the absence of tectonic extension, the heave of the faults must be complemented by horizontal compaction of the sediments. Density inversion, syneresis and low coefficients of friction on fault planes have all been proposed as causal mechanisms for the development of polygonal fault systems, but most sequences that contain polygonal faults are not underla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 45 publications
2
83
0
Order By: Relevance
“…Shin et al [2008] also show that shear displacement can localize under these stress conditions when the sediment exhibits post peak strain softening, and listed multiple soil conditions that exhibit this behavior. Low residual friction on polygonal fault planes is one possible mechanism to explain the displacement accumulation, as identified by Goulty [2002Goulty [ , 2008 and Goulty and Swarbrick [2005]. However, low residual friction does not explain the genesis of faults or the localization of shear into planes, and this model must also explain the magnitude of the observed displacement fields associated with polygonal faults for the range of physical properties that capture the diversity of sediment types in which polygonal faults are hosted.…”
Section: Introductionmentioning
confidence: 99%
“…Shin et al [2008] also show that shear displacement can localize under these stress conditions when the sediment exhibits post peak strain softening, and listed multiple soil conditions that exhibit this behavior. Low residual friction on polygonal fault planes is one possible mechanism to explain the displacement accumulation, as identified by Goulty [2002Goulty [ , 2008 and Goulty and Swarbrick [2005]. However, low residual friction does not explain the genesis of faults or the localization of shear into planes, and this model must also explain the magnitude of the observed displacement fields associated with polygonal faults for the range of physical properties that capture the diversity of sediment types in which polygonal faults are hosted.…”
Section: Introductionmentioning
confidence: 99%
“…The model of low coefficient of friction raised by Goulty [8] may support the function of conduits of polygonal faults as well as conventional faults. It was demonstrated that low coefficients of residual friction in fine-grained sediments might be key to the formation of the polygonal system, and there was no evidence that nucleation of those faults that evolve into polygonal systems differs fundamentally from the processes involved in the nucleation of conventional faults in soft sediments [8].…”
Section: Focused Fluid Flow Associated With Polygonal Faultmentioning
confidence: 95%
“…It was demonstrated that low coefficients of residual friction in fine-grained sediments might be key to the formation of the polygonal system, and there was no evidence that nucleation of those faults that evolve into polygonal systems differs fundamentally from the processes involved in the nucleation of conventional faults in soft sediments [8]. Previous studies show that polygonal faults often initiate at shallow burial depth [2,7,29].…”
Section: Focused Fluid Flow Associated With Polygonal Faultmentioning
confidence: 99%
See 2 more Smart Citations